Existence and Uniqueness of Solutions for Coupled Impulsive Fractional Pantograph Differential Equations with Antiperiodic Boundary Conditions. (17th May 2021) - Guida, Karim; Ibnelazyz, Lahcen; Hilal, Khalid; Melliani, Said
Abstract : In this paper, we investigate the solutions of coupled fractional pantograph differential equations with instantaneous impulses. The work improves some existing results and contributes toward the development of the fractional differential equation theory. We first provide some definitions that will be used throughout the paper; after that, we give the existence and uniqueness results that are based on Banach's contraction principle and Krasnoselskii's fixed point theorem. Two examples are given in the last part to support our study.